Organic fertilization to attenuate water salinity effect on papaya growth - Mônica S. da S. Sousa; Vera L. A. de Lima; Marcos E. B. Brito; Luderlândio de A. Silva; Rômulo C. L. Moreira; Carlos J. A. Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The salinity of water and soil reduces the growth and production of crops, especially the fruit trees, such as papaya. Thus, it is necessary to obtain management alternatives for cultivation under these conditions. Therefore, the objective of this study was to evaluate the growth and phytomass of papaya cultivated under irrigation with saline water and organic fertilization. An experiment was set up using a randomized block design, with the treatments distributed in a 5 x 2 factorial scheme, consisting of five levels of salinity of irrigation water (0.6, 1.2, 1.8, 2.4 and 3.0 dS m-1) and two levels of organic fertilization (10 and 20 L of bovine manure per plant), with three replications, totaling thirty experimental plots. Growth variables of papaya were evaluated. Papaya plants were negatively affected by irrigation water salinity, with a greater effect on the number of leaves and on dry phytomass of leaves, with no effect of bovine manure levels.